All Days 2015
DOI: 10.2118/176102-ms
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Well Cementing Applications by Using Large Particle Sizes of Cement Additives

Abstract: Water-soluble cellulose based polymers such as hydroxyethyl cellulose (HEC), methylhydroxyethyl cellulose (MHEC), and carboxymethylhydroxyethyl cellulose (CMHEC) are commonly used additives to control important cement slurry properties like fluid loss, free fluid, and slurry stability. They typically hydrate quickly after contact with the mix water resulting in instant slurry viscosification and potential mixing difficulties especially at higher loadings. Adding cement dispersants to the cementing system desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These normalized velocity profiles agree with the theoretical prediction of velocity from eq. (2) and demonstrate consistency between the low and high field instruments for a simple Newtonian liquid.…”
Section: Low Field Validationmentioning
confidence: 52%
See 1 more Smart Citation
“…These normalized velocity profiles agree with the theoretical prediction of velocity from eq. (2) and demonstrate consistency between the low and high field instruments for a simple Newtonian liquid.…”
Section: Low Field Validationmentioning
confidence: 52%
“…Transport of suspended non-colloidal solid particles is an important process in many industries, including oil and gas production [1] where the controlled placement of a cement slurry [2] and conveyance of solids by drilling fluids [3] are critical for safe and successful operations. Determining the hydrodynamic properties of non-colloidal large particle (diameter > 200 µm) suspensions is a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that conventional Portland cement had a compressive strength decrease of 21.43%, while calcium-aluminate cement was only 5.16%. In addition, weight control agents, such as fly ash, , slag, , nanoparticles (e.g., microsilicon), , resins, , polymers, and many other swelling agents , can be added to adjust the CaO percentage, improve the cement density, and obtain better cement strength. In recent years, there have been many CO 2 -resistant additives developed to protect conventional Portland cement from acidic corrosion. Vorderbuggen et al and Doan et al developed a cement additive (e.g., hydroxyethylcellulose, methyl hydroxyethylcellulose, and carboxymethyl hydroxyethyl cellulose) that can create an insoluble barrier when it encounters an acid attack. Laboratory tests showed that this additive performed well under specific pressure and temperature in brines saturated with CO 2 for weeks.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
“…In recent years, there have been many CO 2 -resistant additives developed to protect conventional Portland cement from acidic corrosion. Vorderbuggen et al and Doan et al developed a cement additive (e.g., hydroxyethylcellulose, methyl hydroxyethylcellulose, and carboxymethyl hydroxyethyl cellulose) that can create an insoluble barrier when it encounters an acid attack. Laboratory tests showed that this additive performed well under specific pressure and temperature in brines saturated with CO 2 for weeks.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
“…Cellulose materials are often used in cement slurries to prevent fluid loss but have proved to be unreliable in both high-and low-temperatures as well as in areas with a high salt concentration [8]. Examples of cellulose materials commonly used in wellbore cement include hydroxyethyl cellulose (HEC), methyl hydroxyethyl cellulose (MHEC), and carboxymethyl hydroxyethyl cellulose (CMHEC), which when hydrated, immediately increase the slurry viscosity [9]. Cellulose materials can prove problematic in that this increased viscosity can lead to issues with pumping the slurry.…”
Section: Introductionmentioning
confidence: 99%